Implementasi Sistem Informasi Pemerintah Daerah Dalam Penyelenggaraan Manajemen Keuangan Daerah Yang Akuntabilitas Di Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Mandailing Natal - M Fernanda; Aldri Frinaldi; Asnil Asnil (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The demands for transparency and accountability in local government financial reports must be balanced with the existence of a system that regulates and manages regional finances. SIPD (Local Government Information System) is an important thing that needs to be properly implemented in both central and regional government, considering that there are still many violations committed by government officials such as corruption and even government financial reports that get a fair opinion with exceptions, not fair. even a disclaimer. The Mandailing Natal District Government is one of the areas that has implemented the Regional Government Information System (SIPD). Based on this, researchers will examine further the implementation of the SIPD system in the implementation of accountable financial management at the Regional Financial and Asset Management Agency (BPKAD) of Mandailing Natal Regency. From the results of the study it can be concluded that BPKAD Mandailing Natal Regency has implemented the Local Government Information System (SIPD) application which previously used the Regional Management Information System (SIMDA) application to carry out the policies needed to carry out various activities which are programs of the Mandailing Natal Regency Government. . However, because the local government information system (SIPD) is a new application, the implementation process is certainly still a lot of obstacles to get. But with the passage of time, various errors and deficiencies that exist in this system will certainly be corrected and will continue to be upgraded so that the various expectations that underlie the formation of this application will be fulfilled. With the existence of SIPD, the regional financial management of Mandailing Natal Regency can be accessed by various stakeholders online. So that accountability or responsibility prioritizes openness as the basis for accountability so that SIPD can improve services to the community effectively, efficiently and accountably by utilizing information and communication technology.